The effect of intravenous iron therapy on long-term survival in anaemic colorectal cancer patients: Results from a matched cohort study. (June 2018) - Wilson, M.J.; Dekker, J.W.T.; Buettner, S.; Harlaar, J.J.; Jeekel, J.; Schipperus, M.; Zwaginga, J.J.
Abstract: Introduction: Intravenous iron therapy has been shown to be advantageous in treating anaemia and reducing the need for blood transfusions. Iron treatment, however, may also be hazardous by supporting cancer growth. Present clinical study explores, for the first time, the effect of preoperative intravenous iron therapy on tumour prognosis in anaemic colorectal cancer patients. Methods: A retrospective cohort study was performed on consecutive patients who underwent surgery for colorectal cancer between 2010 and 2016 in a single teaching hospital. The primary outcomes were 5-year overall survival (OS) and disease-free survival (DFS). Survival estimates were calculated using the Kaplan-Meier method and patients were matched based on propensity score. Results: 320 (41.0%) of all eligible patients were anaemic, of whom 102 patients received preoperative intravenous iron treatment (31.9%). After propensity score matching 83 patients were included in both intravenous and non-intravenous iron group. The estimated 1-, 3-, and 5-year OS (91.6%, 73.1%, 64.3%, respectively) and DFS (94.5%, 86.7%, 83.4%, respectively) in the intravenous iron group were comparable with the non-intravenous iron group (p = 0.456 and p = 0.240, respectively). In comparing patients with an event (death or recurrence) and no event in the intravenous iron group, a distinct trend was found for decreased transferrin in the event group (median 2.53  g/L vs 2.83  g/L, p = 0.052). Conclusion: The present study illustrates that a dose of 1000–2000 mg preoperative intravenous iron therapy does not have a profound effect on long-term overall and disease-free survival in anaemic colorectal cancer patients. Future randomised trials with sufficient power are required to draw definite conclusions on the safety of intravenous iron therapy.